2023
DOI: 10.3390/cancers15020432
|View full text |Cite
|
Sign up to set email alerts
|

Radiomics Approaches for the Prediction of Pathological Complete Response after Neoadjuvant Treatment in Locally Advanced Rectal Cancer: Ready for Prime Time?

Abstract: In recent years, neoadjuvant therapy of locally advanced rectal cancer has seen tremendous modifications. Adding neoadjuvant chemotherapy before or after chemoradiotherapy significantly increases loco-regional disease-free survival, negative surgical margin rates, and complete response rates. The higher complete rate is particularly clinically meaningful given the possibility of organ preservation in this specific sub-population, without compromising overall survival. However, all locally advanced rectal cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 144 publications
0
8
0
Order By: Relevance
“…Noninvasive assessment of the prognosis of RC is challenging and has always been a research hotspot[ 26 , 27 ]. Research has shown that PNI is not only characterized by tumor cell infiltration and growth along the nerves but also involves an interaction between various neurotrophic and chemotactic factors released from tumor cells and the surrounding microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Noninvasive assessment of the prognosis of RC is challenging and has always been a research hotspot[ 26 , 27 ]. Research has shown that PNI is not only characterized by tumor cell infiltration and growth along the nerves but also involves an interaction between various neurotrophic and chemotactic factors released from tumor cells and the surrounding microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…[ 17 19 ] With the continuous development of radiomics, the application of radiomics in the evaluation of CRC efficacy is gradually increasing. [ 20 ] Shi et al [ 21 ] retrospectively collected T2-weighted Imaging (T2WI), diffusion weighted imaging, and dynamic contrast-enhanced sequences of patients with locally advanced rectal cancer (LARC) who received neoadjuvant chemoradiotherapy (nCRT), and extracted radiomics features from them to predict the pathological complete response of LARC patients after nCRT. The results showed that in the prospective validation set, the radiomics model AUC = 0.84 (95% CI: 0.70–0.94), and the radiomics model could effectively predict pathological complete response after nCRT.…”
Section: Discussionmentioning
confidence: 99%
“…Previous NSCLC radiomic analyses have primarily focused on establishing non-invasive biomarkers for specific clinical endpoints, including diagnosis [ 28 , 29 ], treatment response [ 30 , 31 ], and prognostic assessment [ 32 , 33 ]. While these studies have confirmed that radiomic features can capture relevant molecular biomarkers, their clinical utility could be improved by the fundamental limitation that these imaging features are only modest predictors of specific molecular characteristics.…”
Section: Discussionmentioning
confidence: 99%